Characteristics of Sleep Quality of Nursing Students in Bali During Pandemic Covid-19 - Putu Intan Daryaswanti; Ni Made Diah Pusparini Pendet; Ni Putu Eka Febianingsih (Babali Health, 2021)
Introduction: Corona Virus Disease-19 (COVID-19) has spread to 34 provinces in Indonesia. Indonesia first confirmed the case of COVID-19 in March 2020. The outbreak of the COVID-19 pandemic has made the teaching and learning process shifted to distance teaching. This activity-limiting measure in response to curbing the spread of COVID-19 has caused an unprecedented change in human behavior around the world. One of the changes in human behavior is sleep. Sleep is a physiological process that is highly dependent on the environment and social and varies greatly with stress levels. This study aimed to know the characteristics of sleep quality of nursing students during pandemic Covid-19 in Bali. Methods: This study is a descriptive study using univariate analysis. The population in this study is approximately 1,500 nursing students. Sampling technique used in this research is purposive sampling with 422 sample. Data collection tools in the form of questionnaires that are used is a sleep quality questionnaire from the Pittsburg Sleep Quality Index (PSQI). Results: The results show that most of the nursing students’ age ranged from 15-25 (94.1%), female (79.1%) and currently undergoing Bachelor of Nursing education (68%) and students of Nursing in Bali mostly have poor sleep quality (97.4%). Conclusion: Students of Nursing reported to have poor sleep quality over the last month.